PENGARUH SOCIAL MEDIA MARKETING INSTAGRAM TERHADAP NIAT BELI KONSUMEN PADA KOPI JANJI JIWA - Stefanie Sandra Santoso; Sheellyana Junaedi (Universitas Nusa Cendana, 2021)
This study aims to analyze the effect of Social Media Marketing Activity on Brand Equity, the effect of Brand Equity on e-WOM, the effect of e-WOM on Purchase Intention, and the effect of Social Media Marketing Activity on Purchase Intention This study used purposive sampling with 215 valid questionnaires. Respondents were selected based on determined criteria; respondents who know the social media of Jiwa Jiwa's Instagram and have purchased Janji Jiwa either online or directly to outlets. Partial Least Square was chosen as the method of analysis to evaluate research result. In the first results of this study, it is known that Social Media Marketing Activity has a positive and significant effect on Brand Equity. The results of these two studies show that Brand Equity has a positive and significant effect on e-WOM. The results of these three studies show that e- WOM has a positive and significant effect on Purchase Intention. The results of these four studies show that Social Media Marketing Activity has a positive and significant effect on Purchase Intention. Keywords: Social Media Marketing Activity, Brand Equity, Electronic Word of Mouth, Purchase Intention.